The Return of the Policy That Shall Not Be Named : Principles of Industrial Policy - Cherif, Reda (IMF Working Papers; Working Paper, 2019)
Industrial policy is tainted with bad reputation among policymakers and academics and is often viewed as the road to perdition for developing economies. Yet the success of the Asian Miracles with industrial policy stands as an uncomfortable story that many ignore or claim it cannot be replicated. Using a theory and empirical evidence, we argue that one can learn more from miracles than failures. We suggest three key principles behind their success: (i) the support of domestic producers in sophisticated industries, beyond the initial comparative advantage; (ii) export orientation; and (iii) the pursuit of fierce competition with strict accountability.